Can Rational-Emotive Behavior Therapy (REBT) Reduce Academic Anxiety in High School Students? - Debby Nia Novinta; Endah Mastuti (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Teenagers experience rapid development and growth during high school. During this phase, adolescents experience many challenging changes, including changes in emotional and physical development. If these changes are not properly managed, they can lead to problems such as anxiety. One of the sources of teenage anxiety is their academic problems.